FAKTOR - FAKTOR YANG MEMPENGARUHI STATUS IMUNISASI DASAR PADA ANAK USIA 12 -24 BULAN - Aswan, Yulinda; Simamora, Febrina Anggraini (Jurnal Ilmiah PANNMED (Pharmacist, Analyst, Nurse, Nutrition, Midwivery, Environment, Dentist), 2020)
Immunization is the provision of immunity to children against certain diseases that can be prevented by immunization before the age of 12 months. Complete and regular basic immunizations are obtained when a child is less than 11 months old. Immunization can reduce morbidity and mortality for children by 80-95%. Incomplete basic immunization, maximum can only provide protection against disease that is equal to 25-40%. This study aims to determine the factors that influence mothers towards basic immunization status in children aged 12-24 months in the Labuhan Rasoki Padangsidimpuan Southeast Health Center. This research was conducted using descriptive correlation design with cross sectional approach. The population is all mothers who have children aged 12-24 months and bring their children immunized. The number of samples as many as 40 people with total sampling techniques. The results showed from the demographic data of 40 respondents, the majority of mothers aged ? 30 years as much as 45%, the majority of mothers with secondary education as much as 50%, the majority of multiparous mothers as much as 40%, the majority of middle and upper income mothers as much as 40%, the majority of mothers with less knowledge as much as 67 , 5%, and 60% complete basic childhood immunization status. Chi square statistical test results revealed that there was no significant relationship between factors of age, education, occupation, number of children, income, and mother's knowledge of the basic immunization status in children (p> 0.05). Keywords: Basic immunization, Influencing Factors, Children 12 - 24 Months